Democracy as the Basis for Cultural Education in the Malay Traditional Pre-Wedding Procession in Batam, Riau Islands - Rini Suardi; Indrayuda Indrayuda; Fuji Astuti (International Journal of Educational Dynamics, 2021)
Cecah Inai is one of the processions performed in the Batam Malay Traditional Pre-wedding. Before the procession is carried out, usually in reaching a consensus, democracy is carried out, between Mak-Andam and the bride and groom's family. With the development of the democratic era that occurred in this marriage experienced a shift, where in the democratic era it was carried out through an agreement between the family and community leaders in the form of barter, and if the family did not carry out this Cecah Henna event, social sanctions would be received in society. At this time, democracy is undergoing changes that are only agreed upon by the families of the prospective bride and groom and are adjusted to economic factors or strata in society. If the family has the financial capacity, the family will carry out the pre-wedding procession as a whole and if not, then the procession will only carry out the most important parts, namely Curi Inai and Berandam.